Collaborative Governance Dalam Preservasi Jalan Merbabu Kota Sukabumi - Mutya Firdaus; M. Rijal Amirulloh; Dian Purwanti (Jayapangus Press, 2026)
Road preservation plays an important role in maintaining transportation connectivity and supporting socioeconomic activities in urban areas. The recurring damage to Merbabu Road in Sukabumi City indicates that infrastructure management requires not only technical interventions but also effective collaborative governance among stakeholders. This study aims to analyze the implementation of collaborative governance in the preservation of Merbabu Road using the collaborative governance framework of Ansell and Gash, focusing on stakeholder engagement, shared motivation, and capacity for joint action. A qualitative approach was employed through interviews, observation, and documentation, with informants selected using snowball sampling. Data were analyzed using the interactive model of Miles and Huberman, consisting of data condensation, data presentation, and conclusion drawing. The findings show that collaborative governance has been formally established through stakeholder involvement in planning, implementation, and monitoring activities. However, the collaboration has not yet been fully effective due to limited inter-agency coordination, budget constraints, fragmented information systems, delayed responses to community reports, and inadequate technical capacity. These limitations contribute to recurring road damage and hinder the sustainability of road preservation efforts. The study concludes that strengthening coordination, institutional capacity, information integration, and responsiveness to community participation is essential to improve the effectiveness and sustainability of road preservation in Sukabumi City.